Radical polymerizable composition and polymer thereof

By using a radically polymerizable composition composed of a radically polymerizable compound that is immiscible with water and anions, the problem of difficulty in forming a liquid composition with existing vinyl ionomers has been solved, and liquid ionomers with excellent characteristics have been realized. Physical resin.

CN119343385APending Publication Date: 2025-01-21NIPPON SHOKUBAI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380045903.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-06-09
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

It is difficult for the conventional ethylene-based ionomers to form a liquid composition, and the crosslinking of the polymers is covalently bonded, making it difficult to show the properties of a thermoplastic plasmon.

Method used

A radically polymerizable composition composed of a water-immiscible radically polymerizable compound (A) and anion is used to form a resin with an ionomer structure through radical polymerization.

Benefits of technology

It realizes the formation of liquid ionomer-type resin, has excellent adhesion, tensile properties and thermoplasticity, and is suitable for various printing, coating, bonding and sealing purposes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343385A_ABST
    Figure CN119343385A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a radically polymerizable composition which is liquid and is capable of easily forming a resin having an ionomer-type structure. The present invention pertains to a radically polymerizable composition containing: a radically polymerizable compound (A) that is immiscible with water; and an anion represented by formula (1) (wherein R represents a saturated or unsaturated hydrocarbon group having 10 or less carbon atoms). The content ratio of the anions is 1-120 parts by mass per 100 parts by mass of the water-immiscible radically polymerizable compound (A). # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to free radical polymerizable compositions and polymers thereof. Background Art

[0002] Ionomers are basically resins formed by ion crosslinking of hydrophobic main polymers, and many ionomers have been developed so far. For example, typical ionomers include ethylene ionomers, styrene ionomers, perfluorocarbon ionomers, telechelic ionomers, polyurethane ionomers, etc., which are synthesized by synthesizing a main polymer having an ionizable functional group and then ionizing (neutralizing) it (pages 2 to 6 of Non-Patent Document 1).

[0003] In particular, ethylene-based ionomers are the most industrially practical materials among ionomers, and are resins formed by ion crosslinking molecules of copolymers of ethylene and unsaturated carboxylic acids such as (meth) acrylic acid with metal ions such as sodium and zinc or amines. It is known that, unlike covalently crosslinked products, they are thermoplastic despite being crosslinked products, and exhibit various excellent properties such as transparency, toughness, abrasion resistance, low temperature resistance, solvent resistance, heat sealing, adhesion, and self-healing properties (e.g., page 171 of Non-Patent Document 1, Non-Patent Document 2, and Patent Documents 1 to 3).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-079408

[0007] Patent Document 2: Japanese Patent Application Publication No. 2005-054019

[0008] Patent Document 3: Japanese Patent Application Laid-Open No. 11-029672

[0009] Non-patent literature

[0010] Non-patent document 1: “Development of ionomers and ionic polymer materials” CMC Publishing, 2009

[0011] Non-patent document 2: Journal of the Robotics Society of Japan, Vol. 24, No. 4, p. 442, 2006 Summary of the invention

[0012] Problems to be solved by the invention

[0013] As described above, regarding ethylene-based ionomers, a technique of copolymerizing ethylene / unsaturated carboxylic acid and ionizing the copolymer is known.

[0014] However, conventional ionomers are synthesized by synthesizing a main polymer having an ionizable functional group and then ionizing (neutralizing) the main polymer. Therefore, such resins are poorly soluble in common organic solvents and are difficult to prepare into liquid compositions.

[0015] In addition, a commonly used monomer as a carboxylate having a high radical polymerizability is a metal salt of (meth)acrylic acid, but it is difficult to uniformly dissolve in a low-polarity vinyl compound and liquefy it simply by mixing it with water or a highly polar organic substance.

[0016] In addition, if a nonionic polyfunctional vinyl compound such as polyfunctional (meth)acrylate is used as a monomer, it can be uniformly dissolved in a low-polarity vinyl compound, and its polymer becomes a cross-linked product. However, the cross-linking is covalent, and it is difficult to show the characteristics seen in thermoplastic plasma polymers.

[0017] Therefore, an object of the present invention is to provide a radical polymerizable composition which is in a liquid state and can easily form a resin having an ionomer structure and which can be suitably used in, for example, various printing applications.

[0018] Means for solving problems

[0019] The present inventors have conducted various studies to achieve the above-mentioned object and have come up with the present invention. That is, the object of the present invention is achieved by the following [1] to [4].

[0020] [1] A radical polymerizable composition comprising a water-immiscible radical polymerizable compound (A) and the following formula (1):

[0021] [Chemistry 1]

[0022]

[0023] (wherein R represents a saturated or unsaturated hydrocarbon group having 10 or less carbon atoms), wherein the content ratio of the anion is 1 to 120 parts by mass based on 100 parts by mass of the water-immiscible radical polymerizable compound (A).

[0024] [2] The radical polymerizable composition according to [1] above, wherein R in the formula (1) is an allyl group or a methallyl group.

[0025] [3] The radically polymerizable composition as described in [1] or [2] above, wherein the radically polymerizable composition further contains cations, which are one or more cations selected from the group consisting of metal ions, metal oxide ions and cations containing non-metallic elements of Group 15 of the periodic table.

[0026] [4] A polymer of the radical polymerizable composition according to any one of [1] to [3] above.

[0027] Effects of the Invention

[0028] The radical polymerizable composition disclosed herein is a liquid resin that can easily form an ionomer structure and can provide a cured product having excellent properties such as adhesion, tensile properties, thermoplasticity, etc. Therefore, the radical polymerizable composition disclosed herein can be suitably used for various printing, various coatings, bonding, sealing, three-dimensional modeling, etc. DETAILED DESCRIPTION

[0029] The preferred embodiments of the present invention are described in detail below, but the present invention is not limited to the following descriptions and can be applied with appropriate changes within the scope of the present invention. It should be noted that the preferred embodiments of the present invention described below that are obtained by combining two or more preferred embodiments of the present invention are also equivalent to the preferred embodiments of the present invention. In addition, (meth)acrylic acid refers to acrylic acid or methacrylic acid. (Meth)allyl refers to allyl or methallyl.

[0030] First, the components constituting the radical polymerizable composition of the present disclosure will be described.

[0031] <Radical polymerizable compound (A) not miscible with water>

[0032] In the present invention, in order to obtain an ionomer having an ionomer structure, a radical polymerizable compound (A) that is immiscible with water is used as a main component for forming a polymeric skeleton. Here, "immiscible with water" is determined by whether it can be homogenized when mixed with water in equal amounts. In addition, "homogeneous" means that when the radical polymerizable compound (A) and water are mixed in equal amounts, no precipitate is visually observed and the mixed solution is transparent.

[0033] In addition, the determination can be made by determining whether the polymerization is uniform under the temperature and pressure. The determination can be made at room temperature and pressure. The temperature and pressure during mixing may not be room temperature and pressure. Here, the most preferred temperature and pressure for determination are 20°C and 101.3 kPa.

[0034] The water-immiscible free radical polymerizable compound (A) (hereinafter, sometimes referred to as "polymerizable compound (A)") is a compound that is immiscible with water and has a free radical polymerizable group, and can be classified into a monofunctional type that forms a linear polymer by polymerization and a polyfunctional type that forms a covalently crosslinked body. The free radical polymerizable group can be any unsaturated bond that can undergo free radical polymerization, preferably a carbon-carbon double bond, and more preferably a carbon-carbon double bond that is activated by bonding to a functional group.

[0035] As activated carbon-carbon double bonds, for example, carbon-carbon double bonds bonded to carbonyl groups, carbon-carbon double bonds bonded to cyano groups, carbon-carbon double bonds bonded to nitrogen atoms, carbon-carbon double bonds bonded to aromatic rings, carbon-carbon double bonds bonded to oxygen atoms, carbon-carbon double bonds bonded to carbon-carbon double bonds and conjugated, carbon-carbon double bonds bonded to halogen atoms, etc. can be cited, but the present invention is not limited to the above examples. Among them, carbon-carbon double bonds bonded to carbonyl groups, carbon-carbon double bonds bonded to cyano groups, carbon-carbon double bonds bonded to nitrogen atoms, and carbon-carbon double bonds bonded to aromatic rings are preferred.

[0036] Examples of the compound having a carbon-carbon double bond to which a carbonyl group is bonded include (meth)acrylates, 2-(meth)allyloxymethacrylates, (meth)acrylamides, N-substituted maleimides, maleates, fumarates, itaconates, and the like.

[0037] Examples of the compound having a carbon-carbon double bond to which a cyano group is bonded include (meth)acrylonitrile and 2-cyanoacrylates.

[0038] Examples of the compound having a carbon-carbon double bond to which a nitrogen atom is bonded include N-vinylamides and vinylamines.

[0039] Examples of the compound having a carbon-carbon double bond to which an aromatic ring is bonded include aromatic vinyl groups.

[0040] Examples of the compound having a carbon-carbon double bond to which an oxygen atom is bonded include vinyl esters and vinyl ethers.

[0041] Examples of the compound having a carbon-carbon double bond that is conjugated with a carbon-carbon double bond include 1,3-dienes.

[0042] The present disclosure is not limited to the examples described above.

[0043] Among them, compounds having a carbon-carbon double bond bonded to a carbonyl group are preferred from the aspects of polymerization activity and the diversity of synthesizable structures, and (meth)acrylates and 2-(meth)allyloxymethacrylates are more preferred. In addition, compounds having a carbon-carbon double bond bonded to an aromatic ring are preferred from the aspects of polymerization activity and the ability to effectively introduce a low-polarity structure, and aromatic vinyls are more preferred.

[0044] Hereinafter, specific examples of (meth)acrylates, 2-(meth)allyloxymethacrylates, and aromatic vinyl compounds as the polymerizable compound (A) will be given, but the present disclosure is not limited to the examples.

[0045] Examples of the monofunctional (meth)acrylates include alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, sec-pentyl (meth)acrylate, tert-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, tridecyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; alicyclic esters such as cyclohexyl (meth)acrylate, cyclohexylmethyl (meth)acrylate, 3,5,5-trimethylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, and tricyclodecyl (meth)acrylate; and benzyl (meth)acrylate, Aromatic esters such as phenyl acrylate; esters containing ether structures such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, (3,4-epoxycyclohexyl)methyl (meth)acrylate, and (3-ethyloxetan-3-yl)methyl (meth)acrylate; esters in which hydrogen atoms at the ester site are partially or completely substituted with fluorine atoms such as 2,2,2-trifluoroethyl (meth)acrylate and 2,2,3,3,3-pentafluoropropyl (meth)acrylate; esters in which hydrogen atoms at the ester site are partially or completely substituted with silyl groups or silyloxy groups such as trimethylsilylmethyl (meth)acrylate and 3-[tris(trimethylsilyloxy)silyl]propyl (meth)acrylate; etc., but the present disclosure is not limited to the above examples, as long as it has a (meth)acrylate structure and is not miscible with water.

[0046] Examples of the multifunctional (meth)acrylates include polyols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, bisphenol A alkylene oxide di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Esters; esters of alcohols having a vinyl ether group, such as 2-vinyloxyethyl (meth)acrylate and 2-(vinyloxyethoxy)ethyl (meth)acrylate; oligomers / polymers having a (meth)acrylate structure, such as urethane (meth)acrylate oligomers / polymers, epoxy (meth)acrylate oligomers / polymers, and polyester (meth)acrylate oligomers / polymers; etc., but the present disclosure is not limited to the above examples, as long as it has a (meth)acrylate structure and is not miscible with water.

[0047] Examples of the monofunctional 2-(meth)allyloxymethacrylates include methyl 2-(meth)allyloxymethacrylate, ethyl 2-(meth)allyloxymethacrylate, n-propyl 2-(meth)allyloxymethacrylate, isopropyl 2-(meth)allyloxymethacrylate, n-butyl 2-(meth)allyloxymethacrylate, sec-butyl 2-(meth)allyloxymethacrylate, tert-butyl 2-(meth)allyloxymethacrylate, n-pentyl 2-(meth)allyloxymethacrylate, sec-pentyl 2-(meth)allyloxymethacrylate, tert-pentyl 2-(meth)allyloxymethacrylate, and tert-pentyl 2-(meth)allyloxymethacrylate. 2-(meth)allyloxymethacrylate, 2-ethylhexyl methacrylate, 2-(meth)allyloxymethacrylate, isodecyl methacrylate, tridecyl methacrylate, lauryl methacrylate, stearyl methacrylate, etc.; 2-(meth)allyloxymethacrylate, cyclohexyl methacrylate, cyclohexyl methyl methacrylate, 3,5,5-trimethylcyclohexyl methacrylate, isobornyl methacrylate, adamantyl methacrylate, 2-(meth)allyloxymethacrylate, 2-(meth)allyloxymethacrylate, methyl ... alicyclic esters such as tricyclodecyl 2-(meth)allyloxymethacrylate; aromatic esters such as benzyl 2-(meth)allyloxymethacrylate and phenyl 2-(meth)allyloxymethacrylate; 2-methoxyethyl 2-(meth)allyloxymethacrylate, 2-ethoxyethyl 2-(meth)allyloxymethacrylate, phenoxyethyl 2-(meth)allyloxymethacrylate, tetrahydrofurfuryl 2-(meth)allyloxymethacrylate, glycidyl 2-(meth)allyloxymethacrylate, (3,4-epoxycyclohexyl)methyl 2-(meth)allyloxymethacrylate, (3-ethyloxetane-3- Esters containing an ether structure such as 2-(meth)allyloxymethyl methacrylate; esters in which the hydrogen atoms at the ester site are partially or completely substituted with fluorine atoms such as 2-(meth)allyloxymethacrylate 2,2,2-trifluoroethyl 2-(meth)allyloxymethacrylate and 2,2,3,3,3-pentafluoropropyl 2-(meth)allyloxymethacrylate; esters in which the hydrogen atoms at the ester site are partially or completely substituted with silyl groups or silyloxy groups such as trimethylsilylmethyl 2-(meth)allyloxymethacrylate and 3-[tris(trimethylsilyloxy)silyl]propyl 2-(meth)allyloxymethacrylate; etc., but the present disclosure is not limited to the above examples, as long as it has a 2-(meth)allyloxymethacrylate structure and is not miscible with water.

[0048] Examples of the multifunctional 2-(meth)allyloxymethacrylates include ethylene glycol di(2-(meth)allyloxymethacrylate), propylene glycol di(2-(meth)allyloxymethacrylate), butanediol di(2-(meth)allyloxymethacrylate), hexanediol (2-(meth)allyloxymethacrylate), cyclohexanedimethanol di(2-(meth)allyloxymethacrylate), bisphenol A alkylene oxide di(2-(meth)allyloxymethacrylate), trimethylolpropane tri(2-(meth)allyloxymethacrylate), pentaerythritol tetra(2-(meth)allyloxymethacrylate), dipentaerythritol penta(2-(meth)allyloxymethacrylate), dipentaerythritol Esters of polyols such as hexa(2-(meth)allyloxymethacrylate); esters of alcohols having a vinyl ether group such as 2-vinyloxyethyl 2-(meth)allyloxymethacrylate and 2-(vinyloxyethoxy)ethyl 2-(meth)allyloxymethacrylate; oligomers / polymers having a 2-(meth)allyloxymethacrylate structure such as urethane(2-(meth)allyloxymethacrylate) oligomers / polymers, epoxy(2-(meth)allyloxymethacrylate) oligomers / polymers, and polyester(2-(meth)allyloxymethacrylate) oligomers / polymers; etc., but the present disclosure is not limited to the above examples, as long as it has a 2-(meth)allyloxymethacrylate structure and is not miscible with water.

[0049] Examples of monofunctional or polyfunctional aromatic vinyls include styrene, α-methylstyrene, vinyltoluene, methoxystyrene, divinylbenzene, etc. However, the present disclosure is not limited to the above examples, and any aromatic vinyl group may be used as long as it has a carbon-carbon double bond bonded to an aromatic ring and is immiscible with water.

[0050] The polymerizable compound (A) preferably has 4 to 90 carbon atoms, more preferably 5 to 80 carbon atoms, and even more preferably 6 to 70 carbon atoms, from the viewpoint of being immiscible with water and having low viscosity even in a polyfunctional type.

[0051] The polymerizable compound (A) may be used alone or in combination of two or more kinds depending on the purpose and application.

[0052] From the viewpoint of achieving a good balance between the viscosity of the composition and mechanical properties of the polymer such as toughness, the content of the polymerizable compound (A) is preferably 10 to 97% by mass, more preferably 20 to 94% by mass, and even more preferably 30 to 90% by mass based on 100% by mass of the radical polymerizable composition.

[0053] <Anion represented by formula (1)>

[0054] The radical polymerizable composition of the present disclosure comprises the following formula (1):

[0055] [Chemistry 2]

[0056]

[0057] (wherein R represents a saturated or unsaturated hydrocarbon group having 10 or less carbon atoms).

[0058] Conventional ionomers are synthesized by synthesizing a main polymer having an ionizable functional group and then ionizing (neutralizing) it. Such resins are poorly soluble in common organic solvents and are difficult to prepare into liquid compositions. Moreover, even if they can be liquefied, the resin concentration must be quite low. On the other hand, it is believed that a resin having an ionomer structure can be formed by radically polymerizing a composition composed of a radically polymerizable salt and a low-polarity radically polymerizable compound.

[0059] In addition, although the (meth) acrylic acid metal salts commonly used as free radical polymerizable salts have high free radical polymerizability, they can only be mixed with water or highly polar organic substances, so it is difficult to be uniformly dissolved in low-polar vinyl compounds and liquefied. In addition, although polyvalent acrylic esters can be mixed with low-polar monomers to form crosslinked bodies, the crosslinking is covalent and it is difficult to show the characteristics seen in thermoplastic plasma polymers. In the present invention, by using the above-mentioned anions, it can also be uniformly dissolved with low-polar vinyl compounds and can be made into liquid polymerizable compositions. In addition, by simple methods such as coating and printing processes, resins with ionomer structures can be well formed.

[0060] In order to prepare the radical polymerizable composition of the present invention containing the anion represented by the above formula (1), it is preferred to use a radical polymerizable carboxylate compound (B) composed of an anion component containing the anion represented by the above formula (1) and a cationic component as a component for forming an ionic crosslinking structure. That is, the radical polymerizable composition of the present invention preferably contains a radical polymerizable carboxylate compound (B) composed of an anion and a cation containing at least the anion represented by the above formula (1).

[0061] From the viewpoint of solubility in the polymerizable compound (A) and an organic solvent, R preferably has 3 or more carbon atoms, and more preferably has 3 to 10 carbon atoms. From the viewpoint of forming a polar structure by cyclopolymerization, R is more preferably a (meth)allyl group.

[0062] In the radical polymerizable composition of the present invention, when the content ratio of the anion represented by the above formula (1) is 1 to 120 parts by mass based on 100 parts by mass of the above polymerizable compound (A), the viscosity of the composition and the mechanical properties of the polymer such as toughness can be well balanced.

[0063] The content of the anion represented by the formula (1) is preferably 2 to 115 parts by mass, more preferably 3 to 110 parts by mass, further preferably 10 to 105 parts by mass, and further preferably 20 to 100 parts by mass, based on 100 parts by mass of the polymerizable compound (A).

[0064] In the following, the anion represented by the above formula (1) may be referred to as "2-oxymethacrylic acid ion", and the radically polymerizable carboxylate compound (B) containing the anion represented by the above formula (1) may be referred to as "polymerizable salt compound (B)".

[0065] The polymerizable salt compound (B) may contain only 2-oxymethacrylic acid ions as anions constituting the polymerizable salt compound (B), or may contain 2-oxymethacrylic acid ions and anions other than 2-oxymethacrylic acid ions.

[0066] There are no particular restrictions on anions other than the above-mentioned 2-oxymethacrylic acid ion, but anions of organic protonic acids are preferred from the perspective of solubility in the above-mentioned polymerizable compound (A) and organic solvents. If such anions are specifically indicated by the name of protonic acid, for example, carboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, myristic acid, stearic acid, oxalic acid, malonic acid, succinic acid, adipic acid, cyclohexanetricarboxylic acid, benzoic acid, phthalic acid, terephthalic acid, trimellitic acid, acrylic acid, methacrylic acid, maleic acid, fumaric acid, and itaconic acid; organic phosphoric acids such as 2-ethylhexyl acid phosphate and 2-methacryloyloxyethyl acid phosphate; organic sulfonic acids such as dodecylbenzenesulfonic acid, p-toluenesulfonic acid, 2-acrylamide-2-methylpropanesulfonic acid, and p-styrenesulfonic acid can be cited, but the present disclosure is not limited to the above examples.

[0067] The cation constituting the polymerizable salt compound (B) may be an inorganic cation or an organic cation, and may be appropriately selected according to the purpose and application. The polymerizable salt compound (B) may contain one or more cations.

[0068] That is, the radical polymerizable composition of the present invention may further contain a cation, and the cation is preferably a cation constituting the polymerizable salt compound (B).

[0069] As inorganic cations, metal ions or metal oxide ions can be mentioned. If the element name or metal oxide name is specifically shown, for example, elements of Group 1 of the periodic table such as lithium, sodium, and potassium; elements of Group 2 of the periodic table such as magnesium, calcium, and barium; transition metal elements or transition metal oxides such as lanthanum, zirconium oxide, iron, cobalt, nickel, and copper; typical metal elements of Groups 12 to 15 of the periodic table such as zinc, aluminum, tin, lead, and bismuth; etc., but not limited to the above examples, it can also be a combination of ions of two or more metals or metal oxides. From the aspect of being able to make the polymerizable composition of the present disclosure colorless, as the metal ion part of the carboxylic acid metal salt, ions of typical metal elements, metals belonging to Group 3 and Group 4 of the periodic table, or metal oxides are preferred. If the aspects of availability and toxicity are also considered, lithium, sodium, potassium, magnesium, calcium, zinc, and aluminum are more preferred.

[0070] As organic cations, cations containing non-metallic elements of Group 15 of the periodic table can be cited. As non-metallic elements of Group 15 of the periodic table, nitrogen, phosphorus, and arsenic can be cited. Preferably, ions formed by cationization of nitrogen atoms (ammonium ions, protonated amines, quaternary ammonium ions) and ions formed by cationization of phosphorus atoms (phosphonium ions, protonated phosphine, quaternary ammonium ions) can be cited. From the aspects of biological safety and availability, ions formed by cationization of nitrogen atoms are preferred.

[0071] When the protonated amines are specifically shown by the name of the amine before protonation, for example, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethanolamine, diethanolamine, triethanolamine, tris(2-aminoethyl)amine, hexamethylenediamine, iminobispropylamine, methyliminobispropylamine, 3,6,9,12-tetraoxa-tetradecane-1,14-diamine; N,N'-bis(2-hydroxyethyl)ethanediamine amine, 1,3-bis(aminomethylcyclohexane, 1,4-bis(aminomethylcyclohexane, 3-aminomethyl-3,5,6-trimethylcyclohexylamine, isophoronediamine, 2,5(or 2,6)-bis(aminomethylbicyclo[2,2,1]heptane, 2,6(or 2,7)-bis(aminomethylbicyclo[3,2,1]octane, 2,5(or 2,6)-bis(aminomethyl)-7-dimethylbicyclo[2,2,1] Heptane, 2,6-bis(aminomethyl)adamantane, m-phenylenediamine, p-phenylenediamine, bis(4-aminophenyl)methane, 1,4 (or 2,6 or 2,7)-bis(aminomethyl)naphthalene, diallylamine, piperazine, aminoethylpiperazine, bisaminopropylpiperazine, 2,4,6-triamino-1,3,5-triazine, 2-methylimidazole, 2-ethyl-4-methylimidazole, diazabicycloundecene, diazabicyclononene, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, polyethyleneimine, diallylamine polymers, and various amines having a nitrogen atom moiety having a primary to tertiary structure and an amine number of 1 or more. However, the present disclosure is not limited to the above examples.

[0072] Specific examples of the quaternary ammonium ion include tetramethylammonium ion, tetraethylammonium ion, tetrabutylammonium ion, benzyltrimethylammonium ion, and hexadecyltrimethylammonium ion, but the present disclosure is not limited to these examples.

[0073] The cation is preferably one or more cations selected from the group consisting of metal ions, metal oxide ions, and cations containing non-metallic elements of Group 15 of the periodic table.

[0074] As a method for preparing the polymerizable salt compound (B), preferably, a method comprising at least the following formula (2):

[0075] [Chemistry 3]

[0076]

[0077] (wherein R represents a saturated or unsaturated hydrocarbon group having 10 or less carbon atoms) and neutralize one or more protonic acids of 2-oxymethylacrylic acid with one or more bases. The protonic acid may be completely or partially neutralized. In the case of partial neutralization, a mixture of a salt compound and a protonic acid is generated.

[0078] R in the above formula (2) is the same as R in the above formula (1).

[0079] Examples of the protonic acid that can be used in addition to the 2-oxymethacrylic acid represented by the above formula (2) include the above-mentioned organic protonic acids.

[0080] Examples of the base include inorganic bases such as hydroxides or oxides of metal elements belonging to Groups 1 to 15 of the periodic table, and organic bases containing non-metallic elements of Group 15 of the periodic table such as ammonia, amines, and ammonium hydroxide.

[0081] The neutralization is not particularly limited and can be performed by a known method.

[0082] The radical polymerizable composition of the present disclosure may contain only one type or two or more types of the polymerizable salt compound (B).

[0083] <Other ingredients>

[0084] The polymerizable composition of the present disclosure may contain other components other than the above-mentioned polymerizable compound (A) and the above-mentioned polymerizable salt compound (B) according to its purpose of use, application, etc. Examples of such components include free radical polymerization inhibitors, free radical polymerization initiators, solvents, free radical polymerizable compounds miscible with water, compounds that undergo thermal addition reaction or thermal condensation reaction with active hydrogen groups, thermoplastic resins, organic or inorganic fine particles, fillers, dyes, pigments, dispersants, ultraviolet absorbers, leveling agents, surface conditioners, antistatic agents, adhesion improvers, coupling agents, release agents, viscosity modifiers, etc., but the present disclosure is not limited to these.

[0085] Main components among other components are specifically shown below, but the present disclosure is not limited to the examples.

[0086] [Free Radical Polymerization Inhibitors]

[0087] From the viewpoint of suppressing undesired radical polymerization during storage, transportation, preparation and handling of the composition, the radical polymerizable composition of the present disclosure may contain an appropriate amount of a primary antioxidant having a radical chain reaction preventive property and / or a secondary antioxidant having a peroxide decomposing property.

[0088] Examples of primary antioxidants include hydroquinones, benzoquinones, phenols, aromatic amines, phenothiazines, dithiocarbamate metal salts, and nitroso compounds, but the present disclosure is not limited to the above examples. Examples of secondary antioxidants include phosphorus compounds such as phosphine and phosphite, sulfur compounds such as thioether, mercaptobenzimidazole, and thiourea, but the present disclosure is not limited to the above examples. The primary antioxidant and the secondary antioxidant may be used alone, but are more preferably used in combination.

[0089] Among the primary antioxidants, phenols are preferred from the viewpoint of suppressing coloration, and among the secondary antioxidants, thioethers are preferred from the viewpoint of acid resistance and hydrolysis resistance.

[0090] As phenols, for example, monoether hydroquinones, hindered phenols and polymers (including dimers) or derivatives of polymers, semi-hindered phenols and polymers (including dimers) or derivatives of polymers thereof can be cited, but the present disclosure is not limited to the above examples. These phenols can be used alone or in combination of two or more.

[0091] Examples of monoetherified hydroquinones include hydroquinone monomethyl ether, hydroquinone mono-n-butyl ether, hydroquinone monobenzyl ether, hydroquinone monocyclohexyl ether, and 4-methoxy-1-naphthol, but the present disclosure is not limited to the examples listed above. These monoetherified hydroquinones may be used alone or in combination of two or more.

[0092] Examples of hindered phenols include 2,6-bis(tert-butyl)-4-methylphenol, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, isooctyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, and diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate. However, the present disclosure is not limited to the examples mentioned above.

[0093] Examples of hindered phenol polymers or polymer derivatives include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2-dithiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid amide), 1,6-hexanediolbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, but the present disclosure is not limited to the examples. Hindered phenols and polymers (including dimers) or polymer derivatives thereof may be used alone or in combination of two or more.

[0094] Examples of the semi-hindered phenols include 6-tert-butyl-o-cresol, 6-tert-butyl-2,4-xylenol, 2,4,8,10-tetra-tert-butyl-6-[3-(3-methyl-4-hydroxy-5-tert-butylphenyl)propoxy]dibenzo[d,f][1,3,2]dioxaphosphepine, 2,4-dimethyl-6-(1-methylpentadecyl)phenol, 2,4-bis(octylthiomethyl)o-cresol, 2,4-bis(dodecylthiomethyl)o-cresol, 2-tert-butylphenol, 2,4-di-tert-butylphenol, 2-tert-amylphenol, and 2,4-di-tert-amylphenol. However, the present disclosure is not limited to the examples mentioned above.

[0095] Examples of the polymer or polymer derivative of the semi-hindered phenol include methylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], triethylene glycol bis[β-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 4,4'-thiobis(2-methyl-6-tert-butylphenol), bis(3-methyl-4-hydroxy-5-tert-butylbenzyl)sulfide, terephthaloylbis(2,6-dimethyl-4-tert-butyl-3-hydroxybenzylsulfide), 3,9-bis[2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, 4,4'-thiobis(2-methyl-6-tert-butylphenol), bis(3-methyl-4-hydroxy-5-tert-butylbenzyl)sulfide, terephthaloylbis(2,6-dimethyl-4-tert-butyl-3-hydroxybenzylsulfide), 4'-butylenebis(6-tert-butyl-3-methylphenol), 4,4'-thiobis(6-tert-butyl-3-methylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, etc., but the present disclosure is not limited to the examples. Semi-hindered phenols and polymers (including dimers) or derivatives of polymers may be used alone or in combination of two or more.

[0096] Examples of the phosphine include triethylphosphine, tributylphosphine, tri(2-ethylhexyl)phosphine, and triphenylphosphine, but the present disclosure is not limited to the foregoing examples. These phosphines may be used alone or in combination of two or more.

[0097] Examples of the phosphite include diethyl phosphite, bis(2-ethylhexyl)phosphite, didodecyl phosphite, didoctadecyl phosphite, diphenyl phosphite, triethyl phosphite, tributyl phosphite, tri(2-ethylhexyl)phosphite, triisodecyl phosphite, trilauryl phosphite, tritridecyl phosphite, trioleyl phosphite, tristearyl phosphite, phenyl diisodecyl phosphite, diphenylmethyl phosphite, 2-ethylhexyl phosphite, 1,2-dimethylhexyl diphenyl phosphite, isodecyl diphenyl phosphite, tridecyl diphenyl phosphite, bis(2,4-di-tert-butyl-6-methylphenyl)ethyl phosphite, triphenyl phosphite, tricresyl phosphite, tri(nonylphenyl) phosphite, tri(2,4-di-tert-butylphenyl) phosphite, bis(isodecyl) pentaerythritol diphosphite, bis(tridecyl) pentaerythritol diphosphite, bis(stearyl) pentaerythritol diphosphite, bis(nonylphenyl) pentaerythritol Tetraol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-6-methylphenyl) pentaerythritol diphosphite, 4,4'-butylene bis(3-methyl-6-tert-butylphenyl diisotridecyl) phosphite, tetraphenyl dipropylene glycol diphosphite, tetraphenyl tetra(tridecyl) pentaerythritol tetraphosphite, tetra(C12-C15 alkyl)-4,4'-isopropylidene diphenyl phosphite, tetra(tridecyl) The invention also includes 2,4,8,10-tetra-tert-butyl-6-[3-(3-methyl-4-hydroxy-5-tert-butylphenyl)propoxy]dibenzo[d,f][1,3,2]dioxaphosphophepane, 2,2-methylenebis(4,6-tert-butylphenyl)-2-ethylhexylphosphite, trilauryl trithiophosphite, etc., but the present disclosure is not limited to the above examples. These phosphites can be used alone or in combination of two or more.

[0098] Examples of the thioether include 2,2'-thiodiacetic acid, (ethylenedithio)diacetic acid, 2,2'-(ethylenedithio)diethanol, 3,3'-thiodipropionic acid, dimethyl 3,3'-thiodipropionate, 3-laurylthiopropionic acid, methyl 3-laurylthiopropionate, pentaerythritol tetra(3-octylthiopropionic acid), pentaerythritol tetra(3-decylthiopropionic acid), pentaerythritol tetra(3-laurylthiopropionic acid), pentaerythritol tetra(3-oleylthiopropionic acid), pentaerythritol tetra(3-stearylthiopropionic acid), and pentaerythritol tetra(3-laurylthiopropionic acid). 4,4'-thiobis(3-methyl-5-tert-butyl-4-phenol) ester, dioctyl thiodipropionate, didecyl thiodipropionate, dilauryl thiodipropionate, dimyristyl thiodipropionate, distearyl thiodipropionate, lauryl stearyl thiodipropionate, distearyl-β,β'-thiodibutyrate, dimethyl sulfide, methyl dodecyl sulfide, dilauryl sulfide, distearyl sulfide, 2,4-bis(octylthiomethyl)-o-cresol, 2,4-bis(dodecylthiomethyl)-o-cresol, etc., but the present disclosure is not limited to the examples. These thioethers may be used alone or in combination of two or more.

[0099] From the perspective of suppressing radical polymerization during storage, transportation, composition preparation, and various operations during handling, and also ensuring radical polymerizability corresponding to the intended use, the amount of the radical polymerization inhibitor is preferably 0.005 to 2 parts by mass, more preferably 0.01 to 1 part by mass, and even more preferably 0.02 to 0.5 parts by mass relative to 100 parts by mass of the total radical polymerizable components.

[0100] [Free Radical Polymerization Initiator]

[0101] Radical polymerization initiators can be classified into photoradical initiators that generate radicals by irradiation with active energy rays and thermal radical initiators that generate radicals by heating. The initiator can be selected according to the application and purpose, and a photoradical initiator and a thermal radical initiator can be used in combination.

[0102] As the photoradical initiator, for example, alkylphenone compounds, benzophenone compounds, benzoin compounds, ketal compounds, anthraquinone compounds, phosphine oxide compounds, thioxanthone compounds, halomethylated triazine compounds, halomethylated oxadiazole compounds, biimidazole compounds, oxime ester compounds, titanocene compounds, benzoate compounds, acridine compounds, etc. can be cited, but the present disclosure is not limited to the above examples. These photoradical initiators can be used alone or in combination of two or more.

[0103] Specific examples include acetophenone, 1,1-dichloroacetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylthiophenyl)-2-methyl ... Alkyl phenone compounds such as benzophenone, 4,4'-bis(dimethylamino)benzophenone, 2-carboxybenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, benzoin compounds such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, acetophenone dimethyl ketal, benzyl dimethyl ketal, anthraquinone compounds such as 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-chloroanthraquinone, 2-amylanthraquinone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl phosphine oxide compounds such as 2-aminopentylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide; thioxanthone compounds such as 2-ethylthioxanthone, 2-isopropylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, [3-(3,4-dimethyl-9-oxothioxanthene-2-yl)oxy-2-hydroxypropyl]trimethylammonium chloride; halogenated methyl compounds such as 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-ethoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine and 2-(4-ethoxycarbonylnaphthyl)-4,6-bis(trichloromethyl)-s-triazine triazine compounds; halogenated oxadiazole compounds such as 2-trichloromethyl-5-[β-(2'-benzofuranyl)vinyl]-1,3,4-oxadiazole, 2-trichloromethyl-5-[β-(2'-(6"-benzofuranyl)vinyl)]-1,3,4-oxadiazole, and 2-trichloromethyl-5-furanyl-1,3,4-oxadiazole; biimidazole compounds such as 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4-dichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, and 2,2'-bis(2,4,6-trichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole;Oxime ester compounds such as 1-[4-(phenylthio)-, 2-(O-benzoyloxime)]-1,2-octanedione and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyloxime)ethanone; titanocene compounds such as bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium; acylphosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; benzoate compounds such as p-dimethylaminobenzoic acid and p-diethylaminobenzoic acid; acridine compounds such as 9-phenylacridine; etc., but the present disclosure is not limited to the above examples. ;

[0104] As the thermal radical initiator, an organic peroxide-based initiator and an azo-based initiator are preferred, and specific examples thereof include the following initiators.

[0105] Methyl ethyl ketone peroxide, cyclohexanone peroxide, methyl cyclohexanone peroxide, methyl acetoacetate peroxide, acetoacetate peroxide (acetyl peroxide), 1,1-bis (tert-hexyl peroxy) -3,3,5-trimethylcyclohexane, 1,1-bis (tert-hexyl peroxy) cyclohexane, 1,1-bis (tert-butyl peroxy) -3,3,5-trimethylcyclohexane, 1,1-bis (tert-butyl peroxy) -2-methylcyclohexane, 1,1-bis (tert-butyl peroxy) cyclohexane, 1,1-bis (tert-butyl peroxy) cyclododecane, 1,1-bis (tert-butyl peroxy) butane, 2,2-bis (4,4-di-tert-butylperoxycyclohexyl) propane, terpane hydroperoxide, diisopropylbenzene hydroperoxide, 1, 1,3,3-Tetramethylbutyl hydroperoxide, cumene hydroperoxide, tert-hexyl hydroperoxide, tert-butyl hydroperoxide, α,α'-bis(tert-butylperoxy)diisopropylbenzene, dicumyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-butylcumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-hexyne, isobutyryl peroxide, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, succinic acid peroxide, m-toluoylbenzoyl peroxide, benzoyl peroxide, di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate Ester, di-2-ethoxyethyl peroxydicarbonate, di-2-ethoxyhexyl peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, di(3-methyl-3-methoxybutyl) peroxydicarbonate, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, cumyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, tert-hexyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 2,5-dimethyl-2,5-bis(2-ethylhexanoyl) tert-Butyl peroxymaleate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, tert-butyl peroxy-isopropyl monocarbonate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxyacetate, tert-butyl peroxy-m-tolylbenzoate, tert-butyl peroxybenzoate, bis(tert-butylperoxy)isophthalate, 2,5-dimethyl-2,5-bis(m-tolylperoxy)hexane, tert-hexyl peroxybenzoate, 2,5-dimethyl-2,5-bis(m-tolylperoxy)hexane, tert-hexyl peroxybenzoate, 2,5-dimethyl-2,Organic peroxide initiators such as 5-bis(benzoyl peroxide)hexane, tert-butyl peroxyallyl monocarbonate, tert-butyltrimethylsilyl peroxide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,3-dimethyl-2,3-diphenylbutane.

[0106] 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile, 1-[(1-cyano-1-methylethyl)azo]formamide, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis(2-methyl-N-phenylpropionamidine) dihydrochloride, 2,2'-azobis[N-(4-chlorophenyl)-2-methylpropionamidine] dihydrochloride, 2 ,2'-azobis[N-(4-hydroxyphenyl)-2-methylpropionamidine] dihydrochloride, 2,2'-azobis[2-methyl-N-(phenylmethyl)propionamidine] dihydrochloride, 2,2'-azobis[2-methyl-N-(2-propenyl)propionamidine] dihydrochloride, 2,2'-azobis[N-(2-hydroxyethyl)-2-methylpropionamidine] dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(4,5,6,7-tetrahydro-1H-1,3-diazapine] -2-yl)propane] dihydrochloride, 2,2'-azobis[2-(3,4,5,6-tetrahydropyrimidin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(5-hydroxy-3,4,5,6-tetrahydropyrimidin-2-yl)propane] dihydrochloride, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane} dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl ] propionamide}, 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)ethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis(2-methylpropionamide), 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis(2-methylpropane), dimethyl-2,2-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis[2-(hydroxymethyl)propionitrile] and the like.

[0107] These may be used alone or in combination of two or more.

[0108] The content of the radical polymerization initiator is not particularly limited, but is preferably 0.05 to 10.0 parts by mass, more preferably 0.1 to 7.0 parts by mass, and even more preferably 0.2 to 5.0 parts by mass, based on 100 parts by mass of the total of the radical polymerizable components.

[0109] [Solvent]

[0110] From the viewpoints of adjusting viscosity, adjusting coating film thickness, dissolving resin, and compounding hydrophilic components, an appropriate amount of organic solvent or water may be contained.

[0111] Examples of the organic solvent include monoalcohols such as methanol, ethanol, isopropanol, n-butanol, and sec-butanol; diols such as ethylene glycol and propylene glycol; cyclic ethers such as tetrahydrofuran and dioxane; and diol monoethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, and 3-methoxybutanol. ; Ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol methyl ethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether and other glycol ethers; ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol mono Esters of glycol monoethers such as ethyl ether acetate, propylene glycol monobutyl ether acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, dipropylene glycol monobutyl ether acetate, and 3-methoxybutyl acetate; alkyl esters such as methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl lactate, ethyl lactate, butyl lactate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-ethoxypropionate, methyl acetoacetate, and ethyl acetoacetate; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; aromatic hydrocarbon compounds such as benzene, toluene, xylene, and ethylbenzene; aliphatic hydrocarbon compounds such as hexane, cyclohexane, and octane; amides such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; etc., but the present disclosure is not limited to the examples. These organic solvents may be used alone or in combination of two or more.

[0112] [Water-miscible free radical polymerizable compound]

[0113] The radical polymerizable composition of the present invention may contain a water-miscible radical polymerizable compound in an appropriate amount according to the purpose and use. As the above-mentioned water-miscible radical polymerizable compound, specifically, for example, (meth)acrylic acid, salts of (meth)acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, salts of 2-acrylamide-2-methylpropanesulfonic acid, 2-hydroxyethyl (meth)acrylate, glyceryl mono(meth)acrylate, (meth)acrylamide, acryloylmorpholine, N-vinylacetamide, N-vinylpyrrolidone, polyethylene glycol di(meth)acrylate, etc., as long as it is a compound miscible with water and having a radical polymerizable group.

[0114] [Compounds that undergo thermal addition reaction or thermal condensation reaction with active hydrogen groups]

[0115] The radical polymerizable composition of the present invention may contain an appropriate amount of one or more compounds that undergo thermal addition reaction or thermal condensation reaction with active hydrogen groups in order to improve the heat resistance and hardness of the cured product.

[0116] Such a compound may have any functional group as long as it undergoes a thermal addition reaction or a thermal condensation reaction with an active hydrogen group, and may have only one type or two or more types in the same molecule. Also, may have only one type or two or more types in the same molecule.

[0117] Examples of the functional group that undergoes a thermal addition reaction or a thermal condensation reaction with an active hydrogen group include an epoxy group, an oxetane group, a carbodiimide group, an oxazoline group, an aziridine group, an isocyanate group, an alkoxysilyl group, and a hydroxymethyl group or an alkoxymethyl group bonded to a nitrogen atom. However, the present disclosure is not limited to these examples.

[0118] Examples of the compound having an epoxy group include glycidyl (meth)acrylate, 2-ethylhexyl glycidyl ether, p-tert-butylphenyl glycidyl ether, N-glycidyl phthalimide, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, neopentyl glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, sorbitol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and phenol novolac type polyglycidyl ether. Compounds having a glycidyl group, such as water glyceryl ether, o-cresol novolac type polyglycidyl ether, triglycidyl isocyanurate, 4,4'-methylenebis(N,N-diglycidylaniline); compounds having an alicyclic epoxy group, such as (3,4-epoxycyclohexyl)methyl (meth)acrylate, (3,4-epoxycyclohexylmethyl)3,4-epoxycyclohexanecarboxylate, 1,2-epoxy-4-vinyl-1-cyclohexene, bis(3,4-epoxycyclohexylmethyl)adipate, 4-vinylcyclohexene dioxide; free radical (co)polymers of compounds having a free radical polymerizable group and an epoxy group, such as glycidyl (meth)acrylate and (3,4-epoxycyclohexyl)methyl (meth)acrylate; etc., but the present disclosure is not limited to the above examples.

[0119] Examples of compounds having an oxetane group include low molecular weight compounds such as (3-ethyl-3-oxetane)methyl (meth)acrylate, 3-allyloxymethyl-3-ethyloxetane, 2-ethylhexylmethyl-3-ethyloxetane, bis(3-ethyl-3-oxetanemethyl)ether, bis[(3-ethyl-3-oxetane)methyl]isophthalate, and 4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl; radical (co)polymers of compounds having a radical polymerizable group and an oxetane group such as (3-ethyl-3-oxetane)methyl (meth)acrylate; etc. However, the present disclosure is not limited to the examples described above.

[0120] Examples of compounds having a carbodiimide group include N,N'-diisopropylcarbodiimide, N,N'-di-tert-butylcarbodiimide, N,N'-dicyclohexylcarbodiimide, bis(2,6-diisopropylphenyl)carbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and Carbosista (product name, Teijin Limited). However, the present disclosure is not limited to the examples mentioned above.

[0121] Examples of the compound having an oxazoline group include Epocros WS-300 (product name, Nippon Shokubai Co., Ltd.), Epocros WS-500 (product name, Nippon Shokubai Co., Ltd.), Epocros WS-700 (product name, Nippon Shokubai Co., Ltd.), and Epocros RPS-1005 (product name, Nippon Shokubai Co., Ltd.), but the present disclosure is not limited to the examples mentioned above.

[0122] Examples of the compound having an aziridine group include Chemitite PZ-33 (product name, Nippon Shokubai Co., Ltd.) and Chemitite DZ-22E (product name, Nippon Shokubai Co., Ltd.), but the present disclosure is not limited to these examples.

[0123] As compounds having an isocyanate group, for example, low molecular weight compounds such as (meth) 2-isocyanatoethyl acrylate, toluene diisocyanate, xylylene diisocyanate, bis(isocyanatomethyl)cyclohexane, hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate (monomer MDI) and the like; free radical (co)polymers of compounds having free radical polymerizable groups and isocyanate groups such as polymerized MDI, (meth) 2-isocyanatoethyl acrylate, and isocyanate-terminated prepolymers obtained by reacting polyols with excess polyisocyanates, and the like, but the present disclosure is not limited to the above examples. It should be noted that the isocyanate group may be an isocyanate group masked with a capping agent such as phenol, ε-caprolactam, methyl ethyl ketone oxime, diethyl malonate, ethyl acetoacetate, dimethylpyrazole and the like.

[0124] Examples of the compound having an alkoxysilyl group include tetramethoxysilane, tetraethoxysilane, a hydrolysis / polycondensation oligomer of tetramethoxysilane, a hydrolysis / polycondensation oligomer of tetraethoxysilane, 3-(trimethoxysilyl)propyl (meth)acrylate, 3-[dimethoxy(methyl)silyl]propyl (meth)acrylate, 3-(triethoxysilyl)propyl (meth)acrylate, 3-[diethoxy(methyl)silyl]propyl (meth)acrylate, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)silane, The present invention also includes low molecular weight compounds such as trimethoxysilane, trimethoxysilyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, vinyltrimethoxysilane, vinyltriethoxysilane, tris[3-(trimethoxysilyl)propyl]isocyanurate, bis[3-(trimethoxysilyl)propyl]amine, and 1,6-bis(trimethoxysilyl)hexane; and high molecular weight compounds such as radical (co)polymers of compounds having a radical polymerizable group and an alkoxysilyl group such as terminal alkoxysilyl type polydimethylsiloxane, 3-(trimethoxysilyl)propyl(meth)acrylate, and 3-(triethoxysilyl)propyl(meth)acrylate. However, the present disclosure is not limited to the examples mentioned above.

[0125] Examples of the compound having a hydroxymethyl group or an alkoxymethyl group bonded to a nitrogen atom include hydroxymethylated (meth)acrylamide compounds such as N-(hydroxymethyl)(meth)acrylamide, N-(methoxymethyl)(meth)acrylamide, N-(hydroxymethyl)(meth)acrylamide, or a radical (co)polymer of N-(methoxymethyl)(meth)acrylamide; melamine resins such as hexamethylolmelamine, a partially or completely methylated product of hexamethylolmelamine, partially methylolated melamine, and a methylated product of partially methylolated melamine; benzoguanamine resins such as tetramethylolbenzoguanamine and a methylated product of tetramethylolbenzoguanamine; urea resins such as 1,3,4,6-tetrakis(methoxymethyl)glycoluril, dimethyloldihydroxyethyleneurea, and a methylated product of dimethyloldihydroxyethyleneurea; etc. However, the present disclosure is not limited to the above examples.

[0126] The content of these compounds that undergo thermal addition reaction or thermal condensation reaction with active hydrogen groups may be adjusted depending on the application and purpose, and may not be included. However, when used, it is preferably 1 part by mass or more and 90 parts by mass or less, more preferably 2 parts by mass or more and 85 parts by mass or less, and even more preferably 3 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of the polymerizable composition of the present disclosure.

[0127] <Polymer of the present disclosure>

[0128] The polymer disclosed in the present invention is obtained by reacting the radical polymerizable composition disclosed in the present invention, and the reaction method at least includes generating free radicals in the radical polymerizable composition disclosed in the present invention and subjecting it to free radical polymerization. The polymer obtained by polymerizing the radical polymerizable composition disclosed in the present invention under free radical generating conditions, i.e., the radical polymer of the radical polymerizable composition disclosed in the present invention, is also one of the present invention.

[0129] As a method for generating free radicals, there can be mentioned a method of heating the free radical polymerizable composition of the present invention and / or a method of irradiating the free radical polymerizable composition of the present invention with active energy rays. Heating or irradiation with active energy rays may be performed in one stage or in two or more stages. Heating and irradiation with active energy rays may be combined, combined simultaneously, or separated. When heating or irradiation with active energy rays is performed, the free radical polymerizable composition of the present invention is more preferably in a state containing the above-mentioned free radical polymerization initiator.

[0130] When heating is performed, the temperature may be appropriately selected depending on the presence, type, content and application of a radical polymerization initiator. When a thermal radical initiator is used, the temperature is 40° C. or higher, more preferably 50° C. or higher, and even more preferably 60° C. or higher.

[0131] As the above-mentioned active energy rays, commonly used active energy rays can be used, and electromagnetic waves such as gamma rays, X-rays, ultraviolet rays, visible rays, infrared rays, and particle beams such as electron beams, neutron beams, and proton beams can be cited. Among them, from the aspects of energy intensity and energy ray generation device, gamma rays, X-rays, ultraviolet rays, visible rays, and electron beams are preferred, ultraviolet rays, visible rays, and electron beams are more preferred, and ultraviolet rays are most preferred. In the case of not using a photoradical initiator, it is preferred to use active energy rays with strong energy such as gamma rays, X-rays, and electron beams. In the case of using a photoradical initiator, it is preferred to use active energy rays with relatively weak energy such as ultraviolet rays and visible rays, but easy to generate and economical.

[0132] The reaction for obtaining the polymer of the present disclosure includes at least generating free radicals in the polymerizable composition of the present disclosure and subjecting it to free radical polymerization, but may also include reactions other than these, and as such reactions, preferably, thermal addition reaction with active hydrogen groups and thermal condensation reaction with active hydrogen groups can be cited. These reactions can be carried out before free radical polymerization, can be carried out simultaneously, or can be carried out after. When the thermal addition reaction with active hydrogen groups or the thermal condensation reaction with active hydrogen groups is carried out, the polymerizable composition of the present disclosure is more preferably in a state containing the compound that undergoes thermal addition reaction or thermal condensation reaction with the above-mentioned active hydrogen groups.

[0133] The heating temperature may be appropriately selected depending on the type, content and application of the compound that undergoes thermal addition reaction or thermal condensation reaction with the active hydrogen group, and is 40° C. or higher, more preferably 70° C. or higher, and even more preferably 90° C. or higher.

[0134] The polymer of the present disclosure includes the structural unit (a) derived from the above-mentioned polymerizable compound (A) and the structural unit (b) derived from the above-mentioned 2-oxymethacrylic acid ion, and may further include a structural unit (c) derived from another polymerizable compound.

[0135] The polymer may contain only one type, or two or more types, of each of the structural unit (a), the structural unit (b), and the structural unit (c).

[0136] The preferred content ratio of the structural unit (a) in the polymer is the same as the content ratio of the polymerizable compound (A) in the polymerizable composition of the present disclosure, and the preferred content ratio of the structural unit (b) is the same as the content ratio of the 2-oxymethylacrylate ion in the polymerizable composition of the present disclosure.

[0137] Here, the above-mentioned “structural unit (a) derived from the polymerizable compound (A)” and the above-mentioned “structural unit (b) derived from the 2-oxymethacrylic acid ion” are structural units having the same structure as the structural units contained in the polymer obtained by free radical polymerization of the above-mentioned “polymerizable compound (A)” and the above-mentioned “2-oxymethacrylic acid ion”, respectively.

[0138] It should be noted that the structural unit (a) and the structural unit (b) do not need to be structural units formed by actually free radical polymerization of the polymerizable compound (A) and the 2-oxymethylacrylic acid ion, respectively, and may be structural units formed by other methods, such as a synthesis method, as long as they have the same structure as the structural unit obtained by free radical polymerization.

[0139] Examples of the structural units possessed by the polymerizable compound (A) and the polymerizable composition containing the 2-oxymethacrylic acid ion by free radical polymerization include (i) structural units in which at least one of the carbon-carbon double bonds of the polymerizable compound (A) and the 2-oxymethacrylic acid ion is replaced with a carbon-carbon single bond; and (ii) structural units in which the polymerizable compound (A) and the 2-oxymethacrylic acid ion are cyclopolymerizable compounds, but are not limited to these.

[0140] Examples of the compound containing 2-oxymethacrylic acid ions include the polymerizable salt compound (B).

[0141] <Application of the radical polymerizable composition of the present disclosure>

[0142] The radical polymerizable composition disclosed in the present invention can be made into a liquid that can also be used for various printing applications by adjusting the types and amounts of the above-mentioned polymerizable compound (A), polymerizable salt compound (B) and other components. The polymer can exert various excellent properties that the conventional ionomers have, and thus can be used, for example, for various coatings (anti-crack coatings for brittle films, protective coatings for decorative films, phase difference adjustment coatings, etc.), primers, sealing materials, adhesives, packaging materials, adhesives, various types of three-dimensional modeling (inkjet, SLA, DLP), thermoplastic molding, thermosetting molding, hot melt bonding, optical films, lenses, electronic components, prepregs, dental materials, coatings, printing inks, fiber treatment agents, resist materials for micro-processing, and the like.

[0143] Example

[0144] The present disclosure will be described in more detail below with reference to Examples, but the present disclosure is not limited to these Examples. It should be noted that, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0145] <2-allyloxymethacrylic acid>

[0146] 2-allyloxymethylacrylic acid having a purity of 96.5% was prepared, containing 0.04% (relative to the total liquid volume) of hydroquinone monomethyl ether and 0.06% (relative to the total liquid volume) of 2,2'-(ethylenedithio)diethanol as a radical polymerization inhibitor. The purity was measured using the following capillary electrophoresis system.

[0147] οMeasurement device

[0148] Capillary electrophoresis system Agilent 7100 (Agilent Technologies, Inc.)

[0149] οMeasurement conditions

[0150] The measurement was carried out by an indirect absorption method using a background absorber.

[0151] Capillary: Bubble Cell Fused-Silica Capillary (inner diameter 75 μm × total length 80.5 cm)

[0152] Electrophoresis liquid: electrophoresis liquid for anion analysis (pH = 8.2)

[0153] Applied voltage: -20kV

[0154] οQuantitative methods

[0155] Quantification was performed by the internal standard method based on area ratio (internal standard substance: sodium propionate). Preparation of standard sample: Sodium propionate and the substance to be quantified (sodium salt of carboxylate ion) were dissolved in heavy water. 1 After the molar ratio was quantified by H-NMR, the sample was further diluted with ultrapure water and used as a standard sample for preparing a calibration curve.

[0156] Preparation of measurement samples: The sodium propionate aqueous solution and the test sample were weighed, and diluted with a 0.1-N sodium hydroxide aqueous solution and ultrapure water to prepare the measurement samples.

[0157] <Dissolution of a polymerizable salt in a water-immiscible free-radical polymerizable compound>

[0158] [Example 1-1]

[0159] Into an eggplant-shaped flask equipped with a stirrer, 0.26 g of zinc oxide, 2.8 g of methanol, and 1.04 g of 2-allyloxymethylacrylic acid were added in sequence, and stirred at 50°C for 4 hours to obtain a uniform methanol solution (90 mol% of 2-allyloxymethylacrylic acid was neutralized with zinc). After returning to room temperature, 2.8 g of 2-ethylhexyl acrylate was added, and then the pressure was reduced by a vacuum pump at room temperature to remove methanol. After removing methanol, the content was also a uniform transparent liquid (zinc concentration 5.2%). The results are shown in Table 1.

[0160] [Example 1-2]

[0161] The same procedure as in Example 1-1 was carried out except that 2-ethylhexyl acrylate was replaced with cyclohexyl acrylate to obtain a uniform, transparent liquid composition having a zinc concentration of 5.2%.

[0162] [Comparative Example 1-1]

[0163] 0.22 g of zinc oxide, 2.8 g of methanol, and 0.43 g of acrylic acid were added to an eggplant-shaped flask equipped with a stirrer, and stirred at 50°C for 4 hours to obtain a uniform methanol solution (90 mol% of acrylic acid was neutralized with zinc). After returning to room temperature, 2.8 g of 2-ethylhexyl acrylate was added (in the case of removing methanol, the zinc concentration was 5.2%), and when the methanol was removed by vacuum pump under reduced pressure at room temperature, a white precipitate was generated during the removal of methanol, and a uniform solution was not formed. The results are shown in Table 1.

[0164] [Comparative Example 1-2]

[0165] The same operation as in Comparative Example 1-1 was carried out except that 2-ethylhexyl acrylate was changed to cyclohexyl acrylate. As a result, a white precipitate was generated during the removal of methanol, and a uniform solution was not formed. The results are shown in Table 1.

[0166] [Table 1]

[0167]

[0168] EHA 2-Ethylhexyl Acrylate

[0169] CHA Cyclohexyl Acrylate

[0170] AIO-A2-allyloxy methacrylate

[0171] AIO-Zn2-Allyloxy Zinc Methacrylate

[0172] AA acrylic acid

[0173] AA-Zn Zinc Acrylate

[0174] AIO-2-allyloxymethacrylate ion

[0175] <Polymer properties: Adhesion>

[0176] [Example 2-1]

[0177] 0.29 g of zinc oxide, 2.4 g of ethanol, and 1.05 g of 2-allyloxymethylacrylic acid were added to an eggplant-shaped flask equipped with a stirrer, and stirred at 50° C. for 4 hours to obtain a uniform ethanol solution (100 mol % of 2-allyloxymethylacrylic acid was neutralized with zinc). After returning to room temperature, 1.24 g of 2-ethylhexyl acrylate and 0.07 g of 1-hydroxycyclohexyl phenyl ketone were added and stirred to obtain a composition of an ethanol solution containing 50% of the polymer component.

[0178] The obtained composition was applied to a heat-resistant acrylic resin film (a 140 μm thick film was formed by melt extrusion of pellets obtained by the method described in Manufacturing Example 7 of Japanese Patent Publication No. 2019-179124) using a rod coater No. 4, and then placed on a hot plate at 80°C for 5 minutes for drying. The UV irradiation device (high-pressure mercury lamp, illumination 200 mW / cm 2 ) to polymerize the dried coating, and the cumulative light intensity was 0.6 J / cm 2 The next step is to make it non-sticky.

[0179] The adhesion of the polymerized layer was evaluated according to JIS K 5600-5-6 (cross cut method). That is, the number of squares remaining without peeling or damage in all squares (10×10 squares=100 squares) was evaluated, with the result being 100. The results are shown in Table 2.

[0180] [Example 2-2]

[0181] The composition of the ethanol solution was prepared in the same manner as in Example 2-1 except that 2-ethylhexyl acrylate was replaced with isobornyl acrylate, and the composition was applied on a heat-resistant acrylic resin film and dried. The dried coating film was polymerized using a belt conveyor type UV irradiation device, and the cumulative light intensity was 0.6 J / cm 2 The adhesiveness was evaluated as follows: the number of squares remaining without peeling or damage was 100. The results are summarized in Table 2.

[0182] [Example 2-3]

[0183] Into an eggplant-shaped flask equipped with a stirrer, 0.19 g of zinc oxide, 2.4 g of ethanol, and 1.14 g of 2-allyloxymethylacrylic acid were added in sequence, and stirred at 50° C. for 3 hours to obtain a uniform ethanol solution (60 mol % of 2-allyloxymethylacrylic acid was neutralized with zinc). After returning to room temperature, 0.75 g of cyclohexyl acrylate, 0.5 g of dipentaerythritol hexaacrylate, and 0.07 g of 1-hydroxycyclohexyl phenyl ketone were added and stirred to obtain a composition of an ethanol solution containing 50% of the polymer component.

[0184] The dried coating was formed on a heat-resistant acrylic resin film in the same manner as in Example 2-1, and a belt conveyor-type UV irradiation device was used at a cumulative light intensity of 5 J / cm 2 The dried coating film was polymerized. The adhesion of the polymerized layer was evaluated, and the number of squares remaining without peeling or damage was 100. The results are shown in Table 2.

[0185] [Comparative Example 2-1]

[0186] Instead of zinc 2-allyloxymethacrylate, 1,4-butanediol diacrylate (length between radical polymerizable groups = carbon number 4) is used. This 1,4-butanediol diacrylate is a divalent acrylate that is easily available industrially, is miscible with a radical polymerizable compound that is immiscible with water, and has a short length between radical polymerizable groups.

[0187] That is, 1.2 g of 1,4-butanediol diacrylate, 1.2 g of 2-ethylhexyl acrylate, and 0.07 g of 1-hydroxycyclohexyl phenyl ketone were stirred and mixed, and the resulting uniform transparent liquid composition was applied to a heat-resistant acrylic resin film using a bar coater No. 2. This was polymerized using a belt conveyor type UV irradiation device in the same manner as in Example 2-1. As a result, at an accumulated light intensity of 5 J / cm 2 The next step is to make it non-sticky.

[0188] The adhesion of the polymerized layer was evaluated. As a result, no peeling or damage occurred, and the number of remaining squares was 0. Table 2 shows the results.

[0189] [Comparative Example 2-2]

[0190] A liquid composition was prepared in the same manner as in Comparative Example 2-1 except that 2-ethylhexyl acrylate was replaced with isobornyl acrylate, and the composition was applied onto a heat-resistant acrylic resin film. Polymerization was performed using a belt conveyor type UV irradiation device, and the result was that the accumulated light intensity was 5 J / cm 2 The adhesiveness was evaluated and it was found that the sheet was not tack-free and no peeling or damage occurred, and the number of remaining squares was 0. The results are shown in Table 2.

[0191] [Comparative Example 2-3]

[0192] A liquid composition was prepared in the same manner as in Comparative Example 2-1 except that 0.72 g of cyclohexyl acrylate and 0.48 g of dipentaerythritol hexaacrylate were used instead of 1.2 g of 2-ethylhexyl acrylate, and the composition was applied onto a heat-resistant acrylic resin film. The film was irradiated with a belt conveyor-type UV irradiation device at a cumulative light intensity of 5 J / cm 2 The polymerized layer was polymerized. The adhesion of the polymerized layer was evaluated. As a result, the number of squares remaining without peeling or damage was 22. The results are shown in Table 2.

[0193] [Table 2]

[0194]

[0195] EHA 2-Ethylhexyl Acrylate

[0196] IBOA Isobornyl Acrylate

[0197] CHA Cyclohexyl Acrylate

[0198] DPHA Dipentaerythritol Hexaacrylate

[0199] BDDA 1,4-Butanediol diacrylate

[0200] AIO-A2-allyloxy methacrylate

[0201] AIO-Zn2-Allyloxy Zinc Methacrylate

[0202] AIO-2-allyloxymethacrylate ion

[0203] <Polymer properties: tensile properties>

[0204] [Example 3-1]

[0205] Into an eggplant-shaped flask equipped with a stirrer, 0.12 g of zinc oxide, 3.0 g of methanol, and 1.49 g of 2-allyloxymethylacrylic acid were added in sequence, and stirred at 50° C. for 4 hours to prepare a uniform solution (29 mol % of 2-allyloxymethylacrylic acid was neutralized with zinc). After returning to room temperature, 3.57 g of 2-ethylhexyl acrylate was added, and the pressure was reduced by a vacuum pump at room temperature to remove methanol, and then 0.15 g of 1-hydroxycyclohexyl phenyl ketone was added and stirred and mixed to obtain a polymerizable composition in the form of a uniform transparent liquid.

[0206] A glass plate (15 cm × 7 cm) with a 2 mm thick polypropylene plate attached and an iron plate (15 cm × 7 cm) with a 2 mm thick polypropylene plate attached were placed opposite each other with the polypropylene plate inside, and a 0.5 mm thick silicon wafer cut into a U shape was sandwiched between them as a spacer and fixed with a clamp to form a casting mold. The polymerizable composition was injected into the casting mold and a belt conveyor type UV irradiation device (high pressure mercury lamp, illuminance 200 mW / cm 2 ), from the glass plate side with a cumulative light intensity of 2 J / cm 2 Remove the fixture, remove the plate on one side, and then irradiate with UV at a cumulative light intensity of 1 J / cm 2 The plate and the silicon wafer were removed to obtain a sheet of about 13 cm×5 cm×0.5 mm thick, which was punched out into a dumbbell No. 3 shape (according to JIS K 6251) using a test piece punching machine.

[0207] After measuring the thickness of the center of the test piece, the tensile strength (maximum tensile force until the test piece is cut), Young's modulus, and elongation at break were measured using a tensile tester (grip spacing: 60 mm, tensile speed: 10 mm / min).

[0208] Furthermore, when the remaining piece after preparing the dumbbell-shaped test piece was analyzed by X-ray diffraction, a peak derived from an ion aggregation region specific to ionomers was observed on the low-angle side (2θ=2 to 4°).

[0209] [Example 3-2]

[0210] 1.42 g of 2-allyloxymethylacrylic acid, 3.43 g of 2-ethylhexyl acrylate, and 0.10 g of tris(2-aminoethyl)amine were added to a screw tube equipped with a stirrer and stirred to prepare a uniform solution (29 mol% of 2-allyloxymethylacrylic acid was neutralized with amine). 0.15 g of 1-hydroxycyclohexyl phenyl ketone was further added and stirred to obtain a polymerizable composition in the form of a uniform transparent liquid.

[0211] Using this polymerizable composition, a dumbbell No. 3 test piece was prepared in the same manner as in Example 3-1, and the tensile strength, Young's modulus, and elongation at break were measured.

[0212] [Comparative Example 3-1]

[0213] Instead of zinc 2-allyloxymethacrylate, 1,4-butanediol diacrylate (the length between acryloyloxy groups = 4 carbon atoms) is used. This 1,4-butanediol diacrylate is a divalent acrylate that is easily available industrially, is miscible with a radically polymerizable compound that is immiscible with water, and has a short length between radically polymerizable groups (=acryloyloxy groups).

[0214] That is, 0.5 g of 1,4-butanediol diacrylate, 4.5 g of 2-ethylhexyl acrylate, and 0.15 g of 1-hydroxycyclohexyl phenyl ketone were stirred and mixed to obtain a polymerizable composition. Using this polymerizable composition, a dumbbell-shaped No. 3 test piece was prepared in the same manner as in Example 3-1. Although a tensile test was intended, the strength of the test piece was very weak, so when it was set in the fixture, the part clamped by the fixture broke and the test could not be performed. The results are shown in Table 3.

[0215] [Comparative Example 3-2]

[0216] A polymerizable composition was obtained in the same manner as in Comparative Example 3-1 except that 1.5 g of 1,4-butanediol diacrylate and 3.5 g of 2-ethylhexyl acrylate were used instead of 0.5 g of 1,4-butanediol diacrylate and 4.5 g of 2-ethylhexyl acrylate. A dumbbell-shaped No. 3 test piece was prepared in the same manner as in Example 3-1 using the polymerizable composition, and the tensile strength, Young's modulus, and elongation at break were measured. The results are shown in Table 3.

[0217] [Example 3-3]

[0218] Into an eggplant-shaped flask equipped with a stirrer, 0.79 g of zinc oxide, 9.0 g of methanol, and 4.77 g of 2-allyloxymethylacrylic acid were added in sequence, and stirred at 50° C. for 4 hours to prepare a uniform solution (60 mol % of 2-allyloxymethylacrylic acid was neutralized with zinc). After returning to room temperature, 10.44 g of 2-ethylhexyl acrylate was added, and the pressure was reduced by a vacuum pump at room temperature to remove methanol, thereby obtaining about 16 g of a polymerizable composition without adding an initiator.

[0219] 5.0 g of the mixture was added with 0.15 g of 1-hydroxycyclohexyl phenyl ketone and stirred and mixed, and then a dumbbell No. 3 test piece was prepared in the same manner as in Example 3-1, and the tensile strength, Young's modulus, and elongation at break were measured. The results are shown in Table 3.

[0220] [Examples 3-4]

[0221] 0.10 g of 1-hydroxycyclohexyl phenyl ketone and 0.05 g of tert-butyl peroxy-2-ethylhexanoate were added to the polymerizable composition obtained in Example 3-3 without adding an initiator, and the mixture was stirred and mixed. The obtained mixture was poured into a mold in the same manner as in Example 3-1, and a UV irradiation device with a belt conveyor was used to irradiate the glass plate with a cumulative light intensity of 1 J / cm 2 The mold was directly placed in an oven at 110°C and heated for 1 hour, then the mold was removed to obtain a sheet of about 13 cm × 5 cm × 0.5 mm thick. Then, a dumbbell-shaped No. 3 test piece was prepared in the same manner as in Example 3-1, and the tensile strength, Young's modulus, and elongation at break were measured. The results are shown in Table 3.

[0222] [Examples 3-5]

[0223] To the polymerizable composition obtained in Example 3-3 to which no initiator was added, 0.10 g of t-butyl peroxypivalate and 0.05 g of 1,1-di(tert-hexylperoxy)cyclohexane were added and stirred and mixed to prepare a polymerizable composition.

[0224] Two iron plates (15 cm × 7 cm) with 2 mm thick polypropylene plates attached are placed opposite each other with the polypropylene plates on the inside, and a 0.5 mm thick silicon sheet cut into a U-shape is sandwiched in between as a spacer, and fixed with a clamp to form a casting mold. The polymerizable composition is injected into the casting mold, and the casting mold is then placed in a polypropylene bag and immersed in warm water at 60°C for 2 hours while suspended. Furthermore, after being placed in an oven at 110°C and heated for 1 hour together with the casting mold, the casting mold is removed to obtain a sheet of about 13 cm × 5 cm × 0.5 mm thick. Then, a dumbbell-shaped No. 3 test piece is prepared in the same manner as in Example 3-1, and the tensile strength, Young's modulus, and elongation at break are measured. The results are shown in Table 3.

[0225] [Examples 3-6]

[0226] A polymerizable composition was obtained in the same manner as in Example 3-1 except that 1.53 g of trimethylolpropane adduct of toluene diisocyanate was further included. That is, 0.12 g of zinc oxide, 3.0 g of methanol, and 1.49 g of 2-allyloxymethylacrylic acid were sequentially added to an eggplant-shaped flask equipped with a stirrer, and stirred at 50°C for 4 hours to prepare a uniform solution (29 mol% of 2-allyloxymethylacrylic acid was neutralized with zinc). After returning to room temperature, 3.57 g of 2-ethylhexyl acrylate was added, and the pressure was reduced with a vacuum pump at room temperature. After removing the methanol, 2.04 g of a 75% ethyl acetate solution of trimethylolpropane adduct of toluene diisocyanate was added, and the pressure was reduced with a vacuum pump again at room temperature to remove the ethyl acetate. Finally, 0.15 g of 1-hydroxycyclohexyl phenyl ketone was added and stirred to mix, and a polymerizable composition was obtained in the form of a uniform transparent liquid.

[0227] Using this polymerizable composition, a sheet of about 13 cm × 5 cm × 0.5 mm thick was obtained in the same manner as in Example 3-1. The sheet was cut into two halves (two sheets of about 6.5 cm × 5 cm) using a cutter, and one sheet was placed in an oven at 150°C for 30 minutes to allow the carboxyl group to react with the isocyanate group, and then returned to room temperature. For the unheated sheet, the surface was wiped with a paper handkerchief containing methanol, and it turned white and became sticky. On the other hand, the heated sheet did not turn white or become sticky even when the surface was wiped with a paper handkerchief containing methanol.

[0228] [Table 3]

[0229]

[0230] EHA 2-Ethylhexyl Acrylate

[0231] BDDA 1,4-Butanediol diacrylate

[0232] AIO-A 2-allyloxymethacrylic acid

[0233] AIO-Zn 2-Allyloxy Zinc Methacrylate

[0234] AIO-TAEA 2-allyloxymethacrylic acid, tris(2-aminoethyl)amine salt

[0235] AIO-2-allyloxymethacrylate ion

[0236] The tensile test results of Examples 3-1 to 3-5 and Comparative Examples 3-1 to 3-2 show that the polymer of the present invention has excellent mechanical strength, and the X-ray diffraction results of Example 3-1 show that the polymer of the present invention has an ionomer structure. In addition, it can be seen that Example 3-6 can improve solvent resistance by adding a crosslinking agent that reacts with a carboxyl group in advance and adopting a dual curing system that performs thermal curing after UV curing.

[0237] <Polymer properties: Thermoplasticity>

[0238] [Example 4-1]

[0239] Into an eggplant-shaped flask equipped with a stirrer, 0.12 g of zinc oxide, 3.0 g of methanol, and 1.49 g of 2-allyloxymethylacrylic acid were added in sequence, and stirred at 50° C. for 4 hours to prepare a uniform solution (29 mol % of 2-allyloxymethylacrylic acid was neutralized with zinc). After returning to room temperature, 3.57 g of cyclohexyl acrylate was added, and the pressure was reduced by a vacuum pump at room temperature to remove methanol, and then 0.15 g of 1-hydroxycyclohexyl phenyl ketone was added and stirred and mixed to obtain a polymerizable composition in the form of a uniform transparent liquid.

[0240] A glass plate (15 cm × 7 cm) with a 2 mm thick polypropylene plate attached and an iron plate (15 cm × 7 cm) with a 2 mm thick polypropylene plate attached were placed opposite each other with the polypropylene plate inside, and a 0.5 mm thick silicon wafer cut into a U shape was sandwiched between them as a spacer and fixed with a clamp to form a casting mold. The polymerizable composition was injected into the casting mold and a belt conveyor type UV irradiation device (high pressure mercury lamp, illuminance 200 mW / cm 2 ), from the glass plate side with a cumulative light intensity of 2 J / cm 2 Remove the fixture, remove the plate on one side, and then irradiate with UV at a cumulative light intensity of 1 J / cm 2 UV was irradiated in a manner. A sheet of about 13 cm × 5 cm × 0.5 mm thick obtained by removing the plate and silicon wafer was cut into a strip of 10 cm × 4 cm using a cutter, and the cut end surface was polished. The remaining sheet after cutting was measured for pencil hardness using an electric pencil hardness tester with a load of 750 g, and the result was H.

[0241] Using a tensile testing machine with an oven, a 10 cm × 4 cm strip test piece was stretched under the conditions of a clamp spacing of 60 mm, a stretching speed of 30 mm / min, and an oven temperature of 120°C. The stretching was stopped when the elongation reached 100% (i.e., 2 times stretching), the oven was removed, and the test piece was returned to room temperature before being removed from the clamp. The obtained test piece was transparent.

[0242] The pencil hardness of the test piece after 2-fold stretching was also measured (the scratch scanning direction was a direction perpendicular to the stretching direction), and the result was that it was improved to 2H.

[0243] Table 4 summarizes the weight ratios of the polymer components and the results of thermoplasticity (stretchable by 2 times: ○, unstretchable: ×).

[0244] [Comparative Example 4-1]

[0245] Instead of zinc 2-allyloxymethacrylate, 1,4-butanediol diacrylate (the length between acryloyloxy groups = 4 carbon atoms) is used. This 1,4-butanediol diacrylate is a divalent acrylate that is easily available industrially, is miscible with a radically polymerizable compound that is immiscible with water, and has a short length between radically polymerizable groups (=acryloyloxy groups).

[0246] That is, 1.5 g of 1,4-butanediol diacrylate, 3.5 g of cyclohexyl acrylate, and 0.15 g of 1-hydroxycyclohexyl phenyl ketone were stirred and mixed to obtain a polymerizable composition. Using this polymerizable composition, a 10 cm × 4 cm long strip test piece was prepared in the same manner as in Example 4-1. The remaining piece after the long strip test piece was prepared was measured for pencil hardness using an electric pencil hardness tester with a load of 750 g, and the result was H.

[0247] The long test piece was stretched using a tensile testing machine with an oven at a clamp distance of 60 mm, a tensile speed of 30 mm / min, and an oven temperature of 120° C., and broke when the elongation reached 5%.

[0248] Table 4 summarizes the weight ratios of the polymer components and the results of thermoplasticity (stretchable by 2 times: ○, unstretchable: ×).

[0249] [Example 4-2]

[0250] A 10 cm×4 cm strip-shaped test piece was prepared in the same manner as in Example 4-1 except that benzyl acrylate was used instead of cyclohexyl acrylate.

[0251] The long strip test piece was stretched using a tensile testing machine with an oven at a clamp spacing of 60 mm, a stretching speed of 30 mm / min, and an oven temperature of 80°C. The stretching was stopped when the elongation reached 100% (i.e., 2 times stretching), the oven was removed, and the test piece was returned to room temperature before being removed from the clamp. The obtained test piece was transparent.

[0252] The retardation of the test piece stretched twice was measured at a measuring wavelength of 550 nm using RETS-100 manufactured by Otsuka Electronics Co., Ltd. The result was a positive retardation of 210 nm per 100 μm thickness. The weight ratio of the polymer components and the results of thermoplasticity (stretchable twice: ○, unstretchable: ×) are summarized in Table 4.

[0253] [Comparative Example 4-2]

[0254] A 10 cm×4 cm strip-shaped test piece was prepared in the same manner as in Comparative Example 4-1 except that benzyl acrylate was used instead of cyclohexyl acrylate.

[0255] The long test piece was stretched using a tensile testing machine with an oven at a clamp distance of 60 mm, a tensile speed of 30 mm / min, and an oven temperature of 120° C., and broke when the elongation reached 5%.

[0256] Table 4 summarizes the weight ratios of the polymer components and the results of thermoplasticity (stretchable by 2 times: ○, unstretchable: ×).

[0257] [Example 4-3]

[0258] 0.11 g of calcium hydroxide, 3.0 g of methanol, 1.0 g of ultrapure water, and 1.51 g of 2-allyloxymethylacrylic acid were added to an eggplant-shaped flask equipped with a stirrer, and stirred at 50° C. for 1 hour to prepare a uniform solution (29 mol % of 2-allyloxymethylacrylic acid was neutralized with calcium). After returning to room temperature, 3.53 g of cyclohexyl acrylate was added, and the pressure was reduced by a vacuum pump at room temperature to remove methanol, and then 0.15 g of 1-hydroxycyclohexyl phenyl ketone was added and stirred and mixed to obtain a polymerizable composition in the form of a uniform transparent liquid.

[0259] Using this polymerizable composition, a 10 cm × 4 cm long strip test piece was prepared in the same manner as in Example 4-1. Using a tensile testing machine with an oven, the long strip test piece was stretched under the conditions of a clamp spacing of 60 mm, a stretching speed of 30 mm / min, and an oven temperature of 120°C. The stretching was stopped when the elongation reached 100% (i.e., 2 times stretching), the oven was removed, and the test piece was returned to room temperature before being removed from the clamp. The obtained test piece was transparent.

[0260] Table 4 summarizes the weight ratios of the polymer components and the results of thermoplasticity (stretchable by 2 times: ○, unstretchable: ×).

[0261] [Example 4-4]

[0262] Into an eggplant-shaped flask equipped with a stirrer, 0.34 g of magnesium hydroxide, 2.0 g of methanol, 1.0 g of ultrapure water, and 1.91 g of 2-allyloxymethylacrylic acid were added in sequence, and after stirring at 50° C. for 1 hour to form a uniform solution, the solution was connected to a vacuum pump to remove the methanol. The powder produced by adding acetone to the flask was washed with acetone, and the powder was obtained by vacuum filtration. The mixture was further dried in vacuum at room temperature to obtain a powder of magnesium 2-allyloxymethylacrylate.

[0263] 0.46 g of 2-allyloxymethacrylate magnesium powder, 1.08 g of 2-allyloxymethacrylic acid, and 0.19 g of ultrapure water were added to a threaded tube equipped with a stirring bar, and stirred while heating to 50° C. to make it uniform and transparent. After returning to room temperature, 3.50 g of cyclohexyl acrylate and 0.15 g of 1-hydroxycyclohexyl phenyl ketone were added and stirred and mixed to obtain a polymerizable composition in the form of a uniform and transparent liquid.

[0264] Using this polymerizable composition, a 10 cm × 4 cm long strip test piece was prepared in the same manner as in Example 4-1. Using a tensile testing machine with an oven, the long strip test piece was stretched under the conditions of a clamp spacing of 60 mm, a stretching speed of 30 mm / min, and an oven temperature of 120°C. The stretching was stopped when the elongation reached 100% (i.e., 2 times stretching), the oven was removed, and the test piece was returned to room temperature before being removed from the clamp. The obtained test piece was transparent.

[0265] Table 4 summarizes the weight ratios of the polymer components and the results of thermoplasticity (stretchable by 2 times: ○, unstretchable: ×).

[0266] [Examples 4-5]

[0267] 0.31 g of sodium carbonate, 3.0 g of methanol, 1.0 g of ultrapure water, and 1.49 g of 2-allyloxymethylacrylic acid were added to an eggplant-shaped flask equipped with a stirrer in this order, and stirred at 50° C. for 1 hour to prepare a uniform solution (29 mol % of 2-allyloxymethylacrylic acid was neutralized with sodium). After returning to room temperature, 3.51 g of cyclohexyl acrylate was added, and the pressure was reduced by a vacuum pump at room temperature to remove methanol, and then 0.15 g of 1-hydroxycyclohexyl phenyl ketone was added and stirred and mixed to obtain a polymerizable composition in the form of a uniform transparent liquid.

[0268] Using this polymerizable composition, a 10 cm × 4 cm long strip test piece was prepared in the same manner as in Example 4-1. Using a tensile testing machine with an oven, the long strip test piece was stretched under the conditions of a clamp spacing of 60 mm, a stretching speed of 30 mm / min, and an oven temperature of 120°C. The stretching was stopped when the elongation reached 100% (i.e., 2 times stretching), the oven was removed, and the test piece was returned to room temperature before being removed from the clamp. The obtained test piece was transparent.

[0269] Table 4 summarizes the weight ratios of the polymer components and the results of thermoplasticity (stretchable by 2 times: ○, unstretchable: ×).

[0270] [Examples 4-6]

[0271] 0.11 g of calcium hydroxide, 3.0 g of methanol, 1.0 g of ultrapure water, and 1.51 g of 2-allyloxymethylacrylic acid were added to an eggplant-shaped flask equipped with a stirrer, and stirred at 50° C. for 1 hour to prepare a uniform solution (29 mol % of 2-allyloxymethylacrylic acid was neutralized with calcium). After returning to room temperature, 2.52 g of cyclohexyl acrylate was added, and the pressure was reduced by a vacuum pump at room temperature to remove methanol, and then 1.01 g of (3-ethyloxetane-3-yl)methyl acrylate and 0.15 g of 1-hydroxycyclohexyl phenyl ketone were added and stirred and mixed to obtain a polymerizable composition in the form of a uniform transparent liquid.

[0272] Using this polymerizable composition, a 10 cm × 4 cm long strip test piece was prepared in the same manner as in Example 4-1. Using a tensile testing machine with an oven, the 10 cm × 4 cm long strip test piece was stretched under the conditions of a clamp spacing of 60 mm, a stretching speed of 30 mm / min, and an oven temperature of 120°C. The stretching was stopped when the elongation reached 100% (i.e., 2 times stretching), the oven was removed, and the test piece was returned to room temperature before being removed from the clamp. The test piece obtained was transparent.

[0273] In addition, the pencil hardness of the remaining piece after cutting out the long strip test piece was measured using an electric pencil hardness tester with a load of 750g, and the result was H. When the surface was wiped with a paper handkerchief containing acetone, it was slightly whitened. On the other hand, the pencil hardness of another remaining piece was measured after heating it on a hot plate at 200°C for 5 minutes, and the result was 3H. Even when the surface was wiped with a paper handkerchief containing acetone, it did not whiten.

[0274] Table 4 summarizes the weight ratios of the polymer components and the results of thermoplasticity (stretchable by 2 times: ○, unstretchable: ×).

[0275] [Table 4]

[0276]

[0277] CHA Cyclohexyl Acrylate

[0278] BZA Benzyl Acrylate

[0279] OXEA(3-ethyloxetan-3-yl)methyl acrylate

[0280] BDDA 1,4-Butanediol diacrylate

[0281] AIO-A2-allyloxy methacrylate

[0282] AIO-Zn2-Allyloxy Zinc Methacrylate

[0283] AIO-Ca 2-Allyloxy Calcium Methacrylate

[0284] AIO-Mg 2-Allyloxy Magnesium Methacrylate

[0285] AIO-Na 2-Allyloxy Sodium Methacrylate

[0286] AIO-2-allyloxymethacrylate ion

[0287] From the results of the heating and stretching tests of Examples 4-1 to 4-6 and Comparative Examples 4-1 to 4-2, it can be seen that the polymer of the present invention is a cross-linked body but has thermoplasticity. From the results of the pencil hardness test of Example 4-1, it can be seen that the scratch hardness is improved by heating and stretching, but from the phase difference measurement results of Example 4-2, it can be seen that the phase difference is manifested by heating and stretching. In addition, from Example 4-6, it can be seen that heating and stretching at 120°C can be performed. On the other hand, by heating at 200°C, the oxetane group reacts with the carboxyl group to form a more solid cross-linked body, and the scratch hardness and solvent resistance are improved than before heating.

[0288] <Polymer characteristics: stretchability>

[0289] [Example 5-1]

[0290] A heat-resistant acrylic resin film with a protective film on one side (the pellets obtained by the method described in Manufacturing Example 7 of Japanese Patent Gazette No. 2019-179124 are formed into a 140 μm thick film by a melt extruder, and a polyethylene protective film is attached to one side thereof) is cut into 15 cm × 7 cm, and the protective film side is attached to an iron plate (15 cm × 7 cm) with a weakly adhesive spray adhesive, and then a transparent tape (thickness 50 μm) is attached to the heat-resistant acrylic resin film in a U-shape. The polymerizable composition prepared in the same manner as in Example 4-1 is placed on the part where the transparent tape is not attached, and is clamped with a glass plate (15 cm × 7 cm) attached with a 2 mm thick polypropylene plate, with the polypropylene plate on the inside, and fixed with a clamp while removing bubbles. Using a belt conveyor-type UV irradiation device (high-pressure mercury lamp, illumination 200 mW / cm 2 ), from the glass plate side with a cumulative light intensity of 2 J / cm 2After irradiating UV in a manner, the glass plate and the iron plate are removed, and the transparent tape portion is cut off together with the heat-resistant acrylic resin film, thereby obtaining a long strip of heat-resistant acrylic resin film coated with the polymer of the present invention on one side. Using a tensile testing machine with an oven, the long strip test piece is stretched under the conditions of a clamp spacing of 60 mm, a stretching speed of 300 mm / min, and an oven temperature of 130°C. The stretching is stopped at the stage where the elongation reaches 100% (i.e., 2 times stretching), the oven is removed, and the test piece is removed from the clamp after returning to room temperature. The obtained test piece is transparent, and no peeling is observed between the polymer layer and the heat-resistant acrylic resin film of the substrate.

[0291] In addition, Table 5 summarizes the composition ratios of the polymerizable compositions.

[0292] [Example 5-2]

[0293] 0.007 g of a fluorine-based surfactant (Ftergent 215M, NEOS Co., Ltd.), 0.14 g of zinc oxide, 1.99 g of phenoxyethyl acrylate, and 1.00 g of 2-allyloxymethyl acrylate were added to a threaded tube equipped with a stirrer, and stirred at 50°C for 30 minutes to prepare a uniform solution. 0.25 g of N,N'-bis(2-hydroxyethyl)ethylenediamine was added and stirred to prepare a uniform solution, and then returned to room temperature. Finally, 0.10 g of 1-hydroxycyclohexyl phenyl ketone was added and stirred to obtain a polymerizable composition in the form of a uniform transparent liquid.

[0294] A heat-resistant acrylic resin film with a protective film on one side (a pellet obtained by the method described in Manufacturing Example 7 of Japanese Patent Publication No. 2019-179124 was formed into a 140 μm thick film by a melt extruder, and a polyethylene protective film was attached to one side thereof) was cut into 15 cm × 7 cm, and the protective film side was attached to a glass plate (15 cm × 7 cm) with a weakly adhesive spray adhesive. Then, the polymerizable composition was applied to the heat-resistant acrylic resin film using a rod coater No. 4, and then a belt conveyor-type UV irradiation device (high-pressure mercury lamp, illumination 150 mW / cm 2 ) in a nitrogen atmosphere with an accumulated light intensity of 1 J / cm 2 The surface is non-sticky and hard.

[0295] The coated film was removed from the glass plate and both ends were cut to obtain a long strip of heat-resistant acrylic resin film (10 cm×5 cm) coated with the polymer of the present invention on one side. The long strip test piece was stretched using a tensile tester with an oven (same as above) under the conditions of a clamp spacing of 60 mm, a stretching speed of 300 mm / min, and an oven temperature of 130°C. The stretching was stopped at the stage where the elongation reached 100% (i.e., 2 times stretching), the oven was removed, and the test piece was returned to room temperature before being removed from the clamp. The obtained test piece was transparent, and no peeling was observed between the polymer layer and the heat-resistant acrylic resin film of the substrate.

[0296] In addition, Table 5 summarizes the composition ratios of the polymerizable compositions.

[0297] [Example 5-3]

[0298] 0.009 g of a fluorine-based surfactant (Ftergent 215M, NEOS Co., Ltd.), 0.22 g of zinc oxide, 2.80 g of phenoxyethyl acrylate, 0.80 g of 2-allyloxymethyl acrylate, and 0.39 g of acrylic acid were added to a threaded tube equipped with a stirring bar, and stirred at 50° C. for 30 minutes to prepare a uniform solution. After returning to room temperature, 0.53 g of diallylamine was added and stirred, and finally 0.14 g of 1-hydroxycyclohexyl phenyl ketone was added and stirred to obtain a polymerizable composition in the form of a uniform transparent liquid.

[0299] A heat-resistant acrylic resin film with a protective film on one side (a pellet obtained by the method described in Manufacturing Example 7 of Japanese Patent Publication No. 2019-179124 was formed into a 140 μm thick film by a melt extruder, and a polyethylene protective film was attached to one side thereof) was cut into 15 cm × 7 cm, and the protective film side was attached to a glass plate (15 cm × 7 cm) with a weakly adhesive spray adhesive. Then, the polymerizable composition was applied to the heat-resistant acrylic resin film using a rod coater No. 4, and then a belt conveyor-type UV irradiation device (high-pressure mercury lamp, illumination 150 mW / cm 2 ) in a nitrogen atmosphere with an accumulated light intensity of 1 J / cm 2 The surface is non-sticky and hard.

[0300] The coated film was removed from the glass plate and both ends were cut to obtain a long strip of heat-resistant acrylic resin film (10 cm×5 cm) coated with the polymer of the present invention on one side. The long strip test piece was stretched using a tensile tester with an oven (same as above) under the conditions of a clamp spacing of 60 mm, a stretching speed of 300 mm / min, and an oven temperature of 130°C. The stretching was stopped at the stage where the elongation reached 100% (i.e., 2 times stretching), the oven was removed, and the test piece was returned to room temperature before being removed from the clamp. The obtained test piece was transparent, and no peeling was observed between the polymer layer and the heat-resistant acrylic resin film of the substrate.

[0301] In addition, Table 5 summarizes the composition ratios of the polymerizable compositions.

[0302] [Table 5]

[0303]

[0304] The stretch followability of Examples 5-1 to 5-3 utilizes the adhesion of the polymer of the present invention as shown in Examples 2-1 to 2-3 and the thermoplasticity of the polymer of the present invention as shown in Examples 4-1 to 4-6. That is, it is shown that the coating layer laminated on the substrate can be thermoformed integrally with the substrate although it is a cross-linked body. Therefore, the polymerizable composition of the present invention can be used, for example, for crack prevention coatings of brittle films, protective coatings of decorative films, phase difference adjustment coatings, etc.

Claims

1. A radical polymerizable composition comprising a water-immiscible radical polymerizable compound (A) and an anion represented by the following formula (1), [Chemistry 1] In the formula, R represents a saturated or unsaturated hydrocarbon group having 10 or less carbon atoms, The content ratio of the anion is 1 to 120 parts by mass based on 100 parts by mass of the water-immiscible radical polymerizable compound (A).

2. The radical polymerizable composition according to claim 1, wherein In the formula (1), R is an allyl group or a methallyl group.

3. The radical polymerizable composition according to claim 1 or 2, wherein The free radical polymerizable composition further comprises a cation, The cations include one or more cations selected from the group consisting of metal ions, metal oxide ions, and cations including non-metallic elements of Group 15 of the periodic table.

4. The polymer of the radical polymerizable composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Ionomer composition

    JP1999029672A

  • Ethylene copolymer composition

    JP2005054019A

  • Method for producing ethylenic ionomer, and the ethylenic ionomer

    JP2016079408A

  • Optical molding body and optical product

    JP2019179124A